Integrated rice husk biochar and compost to improve acid sulfate soil properties and corn growth - Maharani, Puspita Harum; Maftu'ah, Eni; Sulaeman, Yiyi; Napisah, Khairatun; Masganti, Masganti; Mukhlis, Mukhlis; Anwar, Khairil; Ningsih, Rina Dirgahayu; Chairuman, Novia (Journal of Degraded and Mining Lands Management, 2025)
Acid sulfate soils are of poor quality and characterized by extreme acidity, nutrient deficiency, and high Al and Fe toxicity. Developing soil amendments from local resources is crucial to reduce input costs. This study investigated the effect of the integrated soil amendments (biochar, compost, and lime) on corn growth and the acid sulfate soil quality. Using randomized block design, this study tested nine type soil amendments, namely A (100% rice husk ash), B (100% rice husk biochar), C (100% compost), D (100% dolomite), H (100% humate), ACD (30% rice husk ash + 30% compost + 40% dolomite), BCD (30% rice husk biochar + 30% compost + 40% dolomite), AHD (30% rice husk ash + 30% humate + 40% dolomite), BHD (30% rice husk biochar+30% humate+40% dolomite), and control (no amendment). The application of soil amendments significantly increased soil pH (31%), available P (310%), reduced exchangeable Al (19%), and increased corn growth (163%). The BCD amendment type increased available phosphorus from 10 to 43 mg kg-1, reduced exchangeable Al from 3.45 to 2.01 cmol(+) kg-1, and enhanced corn growth and leaves' P level. Integrating rice husk biochar and compost could reduce the need for agricultural lime, improve acid sulfate soil quality, and enhance land productivity. This combination has the potential to be an effective soil amendment for degraded acid sulfate soils, thereby further boosting land productivity and promoting agricultural sustainability.